Development of 1500-m pacing behavior in junior speed skaters: A longitudinal study - Wiersma, R.; Stoter, I. K.; Visscher, C.; Hettinga, F. J.; Elferink-Gemser, M. T. (International Journal of Sports Physiology and Performance, 2017)
Purpose: